Do Pro-Poor Policies Increase Water Coverage? An Analysis of Service Delivery in Kampala's Informal Settlements - World Bank (Washington, DC, 2014)
Uganda is one of the poorest countries in Africa with a gross national income (GNI) per capita in 2010 of United States (U.S.) $500 compared with the Sub-Saharan regional average of $1,170. Uganda's population growth of over 3 percent per year, one of the highest in the world, puts a considerable strain on public sector service delivery, not just for water and sanitation but also in other areas such as health, education, and transport. The aim of this study is to assess the impact of the pro-poor policies introduced by the National Water and Sewerage Corporation (NWSC) between 2004 and 2010, by analyzing the effectiveness, efficiency, and equity of these policies and strategies implemented by the Government of Uganda (GoU) and NWSC to increase coverage of urban water supply services in poor settlements. The study focuses exclusively on the area of Kampala city, the capital of Uganda, as this constitutes the largest service area of the NWSC - with approximately 60 percent of its connections and 64 percent of its revenues. The assessment of the impact of the pro-poor policies on the poor in Kampala is based on an analysis of the effectiveness, the efficiency, and the equity of these policies since 2004. The report is divided into the following six chapters: chapter one gives the introduction of the report and presents the objectives and methods used. Chapter two presents an overview of the water sector in Kampala, including the legal, institutional, and regulatory framework, a definition of poverty in Kampala and what this means for poor households. Chapter three describes the urban water sector policy and the strategy developed by the NWSC to expand services and improve financial performance. Chapter four analyzes in detail the impact of NWSC policies and water supply delivery mechanisms on services to poor households in Kampala. Chapter five contains the conclusions of the study. Chapter six contains recommendations for further analysis which can be undertaken by the NWSC, GoU, and or the World Bank.